An examination of the current knowledge on the stock structure of sperm whales (Physeter macrocephalus) worldwide - Dufault, S.; Whitehead, H.; Dillon, D. (J. Cetacean Res. Manage., 1999)
There is no clear picture of the worldwide stock structure of sperm whales in spite of a great deal of effort, especially in areas where there has been substantial modern whaling. Techniques to examine stock structure have included: the interpretation of catch and sighting distributions and catch per unit of effort; morphological examinations; biochemical and genetic analyses; comparisons of life history parameters; mark-recapture using artificial and natural marks; the occurrence of parasitic infestations; and the comparison of vocal repertoires. Methods which depended on the whaling industry were often limited by unequal distribution of effort and lack of standardised collection methods. Also, most analyses failed to consider the effect of social groupings. Recent research, independent of the whaling industry, has addressed some of these problems. However, the results are equally inconsistent. Variation between the results of different studies can be explained, at least partially, by the temporal scales of the measures used. In general, groups of female and immature sperm whales appear to be restricted to ranges of about 1,000km over periods of 10 years or so. Occasionally, they move much further. Male ranges are generally larger, especially latitudinally. Occasional movements across, and sometimes between, ocean basins seem to have resulted in remarkable global genetic uniformity. To effectively conserve and manage sperm whales in the face of substantial anthropogenic disturbance, we need new and good information on modal and exceptional movement patterns over a range of timescales.